ChemInform Abstract: [1, 5]‐Anion Relay via Intramolecular Proton Transfer to Generate 3, 3‐Bis(silyl) Allyloxy Lithium: A Useful Scaffold for Syn‐Addition to Aldehydes and Ketones. Issue 32 (24th July 2014) - Lin, Xinglong; Ye, Xincui; Sun, Xianwei; Zhang, Yuebao; Gao, Lu; Song, Zhenlei
Abstract The reaction proceeds via [1, 5]‐anion relay in 3, 3‐bis(silyl) benzyl enol ether.